Hungary : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper assesses recent trends in Hungary's potential growth and medium-term growth prospects. It analyzes to what extent the recent moderation of GDP growth reflects structural factors. The paper lays out some stylized facts about the Hungarian economy that could explain the growth slowdown observed in recent years. It provides estimates of potential growth using various methods, identifies the sources of the growth slowdown, and offers forecasts of potential growth over the medium-term under the baseline scenario. A model-based approach is also employed to estimate potential growth over the medium term under a reform scenario.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet